Experiments and a simplified theoretical model for a water-cooled, stove-powered thermoelectric generator. (15th October 2019) - Li, Guoneng; Zheng, Youqu; Hu, Jiangen; Guo, Wenwen
Abstract: A water-cooled, stove-powered thermoelectric generator was designed and tested to provide electricity in off-grid areas and under emergency conditions. An Ω-shaped heat collector, which facilitates the compact incorporation of 20 thermoelectric modules and works under the radiation heat transfer mode, was proposed. A power load test was performed and compared with previous studies, thereby indicating that a standardization is required for future studies. Different aspects for evaluating the performance of a stove-powered thermoelectric generator were discussed, and appropriate parameters to qualify a stove-powered thermoelectric generator were suggested. Thermoelectric efficiency was measured and compared with a theoretical prediction. A simplified theoretical model, which was verified with experimental data, was developed to explore the temperature distribution inside the thermoelectric module and the power generation performance of the entire stove-powered thermoelectric generator. Special efforts were exerted to reveal the influences of thermal grease, ceramic substrate, and thermal contact on the effective temperature difference. Highlights: A novel heat collector based on radiation heat transfer was proposed. Over 50 W electric power can be outputted at a constant voltage of 12 V. The thermoelectric efficiency of the present thermoelectric generator is 3.66%. A model was developed to predict temperature distribution and power generation.